Dampak Penerapan Experiential Learning terhadap Pengembangan Kesadaran Diri Siswa Sekolah Dasar dalam Pembelajaran PJOK - Anton Hilman; Iis Marwan; Juhrodin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of implementing the Experiential Learning model on students’ self-awareness in physical education (PJOK) by comparing learning outcomes between the experimental group and the control group. The method used is a quantitative approach with a pretest-posttest control group design, involving 27 students in the experimental class and 27 students in the control class at SD Negeri Margajaya, Pagerageung District, Tasikmalaya Regency. The self-awareness instrument was developed based on indicators of emotional awareness, accurate self-assessment, and self-confidence. The results show that the data are normally distributed and that the variances of both groups are homogeneous based on normality and homogeneity tests. The independent samples t-test indicates a highly significant difference between the two groups (t = 33.594; p = 0.000), with the experimental group having a mean score of 97.22 and the control group 75.85. These findings indicate that the Experiential Learning model effectively enhances students’ self-awareness, including the ability to recognize and regulate emotions, accurately assess one’s abilities and limitations, and improve self-confidence in physical education activities. In conclusion, the Experiential Learning model is effective in improving students’ self-awareness and can be recommended as a learning approach that optimally develops students’ personal and social aspects.   Keywords: Experiential Learning, Physical Education Learning, Primary School, Self-Awareness